Ribosomal protein S17 gene (RPS17) is mutated in Diamond-Blackfan anemia - Čmejla, Radek; Čmejlová, Jana; Handrková, Helena; Petrák, Jiří; Pospíšilová, Dagmar (Human mutation, 2007)
Diamond-Blackfan anemia (DBA) is a congenital erythroid aplasia characterized as a normochromic macrocytic anemia with a selective deficiency in red blood cell precursors in otherwise normocellular bone marrow. In 40% of DBA patients, various physical anomalies are also present. Currently two genes are associated with the DBA phenotype--the ribosomal protein (RP) S19 mutated in 25% of DBA patients and RPS24 mutated in approximately 1.4% of DBA patients. Here we report the identification of a mutation in yet another ribosomal protein, RPS17. The mutation affects the translation initiation start codon, changing T to G (c.2T>G), thus eliminating the natural start of RPS17 protein biosynthesis. RNA analysis revealed that the mutated allele was expressed, and the next downstream start codon located at position +158 should give rise to a short peptide of only four amino acids (Met-Ser-Arg-Ile). The mutation arose de novo, since all healthy family members carry the wild-type alleles. The identification of a mutation in the third RP of the small ribosomal subunit in DBA patients further supports the theory that impaired translation may be the main cause of DBA pathogenesis. (c) 2007 Wiley-Liss, Inc.
Keywords: Diamondova-Blackfanova anemie; Mutation; kodon iniciační; Financing, Organized; lidé; financování organizované; Ribosomal Proteins; Adult; mutace; Male; malé podjednotky ribozomu; ribozomální proteiny; dospělí; Anemia, Diamond-Blackfan; Humans; Ribosome Subunits, Small; mužské pohlaví; Codon, Initiator